Pengetahuan sebagai Mediasi Intensitas Penyuluhan Terhadap Persepsi Peternak pada Penggunaan Serbuk Daun Nangka sebagai Obat Cacing pada Domba - Nurdayati Nurdayati; Budi Purwo Widiarso; Dhestalia Eka Pratiwi; Fabiana Mentari Putri Wijaya (Department of Communication and Community Development Sciences and PAPPI (Perhimpunan Ahli Penyuluh Pertanian Indonesia), 2021)
The study was carried out in Banter Hamlet, Gumelem Village, Pakis District, Magelang District. The purpose is to determine the farmers' perceptions about the prevention of Haemonchosis using jackfruit leaves powder and to determine the effect of the counseling intensity and the knowledge level of farmers on farmers' perceptions. A sampling of 32 breeders from Ngudi Rejeki 1 Farmer Group was carried out using census method. Data collection techniques were carried out by observation and interview methods. This study was conducted by descriptive analysis using Likert scale to determine the perception level and path analysis to see the perception effect as an endogenous variable with the counseling intensity and knowledge level as exogenous variables. Based on the study, it can be concluded that the descriptive analysis shows farmers' perceptions about the prevention of Haemonchosis using jackfruit leaves powder is in the agree category. The path analysis shows that the counseling intensity does not have a direct effect on perceptions while indirectly from the counseling intensity through the knowledge level significantly influence the perception, so that the knowledge can be said to mediate the counseling intensity on the perception.